Diagnosis of Fasciola gigantica infection in cattle using capture-ELISA assay for detecting antigen in faeces - Sarwitri Endah Estuningsih (Indonesian Center for Animal Research and Development (ICARD), 2006)
Capture-ELISA assay is a diagnosis for antigen detection in the serum or faeces using polyclonal or monoclonal antibodies. The purpose of this study was to determine the sensitivity and specificity of capture-ELISA assay using polyclonal antibody for diagnosing Fasciola gigantica infection in cattle by detecting antigen in the faeces. In this study, faecal samples and livers were collected from 141 cattle slaughtered in the abattoir in Jakarta. From each animal, liver was processed for liver flukes count and the corresponding faecal sample was analysed for coproantigen. The result of capture-ELISA assay for antigen detection showed that from 85 cattle infected with Fasciola gigantica, 83 had OD > 0.52 (range from 0.52-1.39) and 2 cattle had OD < 0.52 (range from 0.17-0.51). The sensitivity and specificity of the assay were 97.6% and 92.8% respectively. The assay also able to detect 50 ng/ml of antigen in faecal supernatant. It suggests that this assay will have the advantage over the other methods on its ability to detect the active infection. Collection of faeces, rather than serum, will allow a more cost-effective and adaptable method. Key Words: Fasciola gigantica, Diagnosis, Capture-ELISA, Antigen